TINJAUAN KUALITATIF USAHA MIKRO KECIL DAN MENENGAH DI KOTA SEMARANG - Violinda, Qristin; Indriasari, Ika; Saraswati, Novi (Politeknik Negeri Lhokseumawe, 2024)
Abstratc : This research aims to deeply understand the conditions and dynamics of Micro, Small, and Medium Enterprises (MSMEs) in Semarang City. Special focus is given to aspects such as business development strategies, challenges faced, and factors that support and hinder the growth of MSMEs in this region. The research uses a qualitative approach with a case study method. Data were collected through in-depth interviews with owners and managers of MSMEs in Semarang City, direct observation, and analysis of related documents. The research sample was chosen through purposive sampling, considering the diversity of business types and locations. MSME actors in Semarang City experienced a decline in business revenue received. This is due to small business operators losing competition to entrepreneurs who have more capital, and most of them also only produce goods when there are orders. Top of FormKeyword : Performance decline, MSMEs (Micro, Small, and Medium Enterprises), Strategies and Factors UMKM